Nasal paraganglioma: a case report and literature review - Granato,Lídio (2013)
INTRODUCTION: Paragangliomas are neuroendocrine tumors that most commonly originate in the adrenal gland, a type that is called pheochromocytoma; however, 5-10% of paragangliomas are extra-adrenal and may arise in any area between the neck and pelvic region along the sympathetic nervous system. Those located in the head and neck comprise 3% of extra-adrenal tumors, with the majority originating in the tympanic-jugular region and carotid body. OBJECTIVE: To present a rare case of nasal paraganglioma and review the literature. CASE REPORT: The patient was submitted to medial subtotal maxillectomy, and her clinical findings, diagnostic data, and treatment outcome were recorded. CONCLUSION: Paragangliomas are considered benign tumors, but they occasionally display a malignant character. The most important finding in this case was the need for total resection of the tumor to avoid recurrence.